2021
DOI: 10.3991/ijim.v15i11.20753
|View full text |Cite
|
Sign up to set email alerts
|

Flashover Prevention System using IoT and Machine Learning for Transmission and Distribution Lines

Abstract: Flashover on transmission and distribution line insulators occurs when the insulator’s resistance drops to a critical level and causes frequent power outages. Thin layers of dust, salt, and airborne particles, gradually deposited on the surface of insulators, as well as humidity, form an electrolyte which causes flashover.  In this paper, a flashover prevention system using IoT technology and machine learning is proposed in order to reduce loss and increase power reliability. The system includes an IoT module,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This helped us to accurately identify the eight activities where some of them are difficult to distinguish between for the similarities among them. Different traditional and Deep learning algorithms have been applied to our dataset as found useful in several machine learning related works [39][40][41][42]. Among them, Bi-directional LSTM gives optimal accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…This helped us to accurately identify the eight activities where some of them are difficult to distinguish between for the similarities among them. Different traditional and Deep learning algorithms have been applied to our dataset as found useful in several machine learning related works [39][40][41][42]. Among them, Bi-directional LSTM gives optimal accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There has been interestingly few studies on the use of machine learning and deep learning models with LoRa RSS datasets in the literature [9][10]. There are four separate data sets based on different RF factors and bandwidths.…”
Section: Training Datamentioning
confidence: 99%
“…It showed that LSTM-MVR Model had improved the operation of forecasting air pollution when compared to LSTM. Furthermore, another study forecasted air pollution based on machine learning techniques [12], it suggested two models: MLP and LSTM models. It confirmed that the LSTM model worked better than the MLP model.…”
Section: Deep Learning Approachmentioning
confidence: 99%